O comportamento de busca de informação dos profissionais médicos em um hospital universitário público brasileiro - Marcelo Novaes Machado (2014)
The study analyzes information needs and sources used by medical professionals at a public university hospital in the state of Minas Gerais, Brazil. The research was carried out in two phases, a quantitative and a qualitative one. The quantitative stage consisted of the application of an electronic questionnaire to such professionals. The results obtained in the first stage were then analyzed in individual interviews with eight respondents. These procedures allowed the identification of the main information needs of such professionals, as well as the contextual factors and demographic variables associated to the information search processes adopted. The sources most frequently used, the influence of job characteristics, as well as the difficulties faced by the participants of the study in their search for information were also identified.